The impact of the Internet on the news media - Beckett, Charlie (Henry Stewart Talks, 2010)
How new media technologies and practices change journalism production and consumption, How public participation is creating networked journalism, Practical and ethical implications for the news media, Strategic business and policy decisions to be taken to promote socially valuable journalism
Archived at 2022/04/12